Cyber security breaches survey, 2023 (UK Data Service, 2023)
The Cyber Security Breaches Survey, 2023 (CSBS) was run to understand organisations' approaches and attitudes to cyber security, and to understand their experience of cyber security breaches. The aim of the survey was to support the Government by providing evidence that can inform policies which help to make Britain a safer place to do business online. Details of changes for the 2023 survey can be found in the Technical Annex documentation. These surveys have been conducted annually since 2016 to understand the views of UK organisations on cyber security. Data are collected on topics including online use; attitudes of organisations to cyber security and awareness of Government initiatives; approaches to cyber security (including investment and processes); incidences and impact of a cyber security breach or attack; and how breaches are dealt with by the organisation. This information helps to inform Government policy towards organisations, including how best to target key messages to businesses and charities so that they are cyber secure (and so that the UK is the safest place in the world to do business online). The study is funded by the DSIT as part of the National Cyber Security Programme. The underlying data are useful for researchers to better understand the response across a range of organisations and for wider comparability over time. The survey originally only covered businesses but was expanded to include charities from the 2018 survey onwards. From 2020, the survey includes a sample of education institutions (primary and secondary schools, further and higher education). Please note that the UK Data Service only holds data from 2018 onwards. For the second edition (August 2023), the data file has been updated to correct an error with the variable COUNTRY. In the earlier version, some non-charity data had been mistakenly mapped to a country in this variable, which refers to charities sampled only. These respondents have now been recoded as -1 (missing).